Application of Open Building Theory in the Regeneration of Old Residential Building. Issue 4 (1st November 2022) - Hai, M; Zhou, B; Fan, Y; Li, Z
Abstract: This research is based on the refinement and diversification demand of housing stock quality improving in China. The paper focuses on the complexity of built environment in old residential areas, which involves numerous responsibilities and rights and multi-role cooperation in the process of regeneration. This paper studies the application of open building theory and its derivative theories in the area of housing regeneration, researches the current situation of policies, mechanisms and design methods for the regeneration of old residential areas in China and discusses the theoretical applicability of open building theory in the design practice of old residential building renewal methods in China. The study investigates the situation of the old residential areas in renovation, divides the responsibility and right relationship between the participants and building components by levels, and establishes a localized theoretical model for the regeneration strategy design of the old residential buildings in China. This study will provide scientific theoretical support for the constructing of a sustainable mechanism involving professional decision-making, long-term management and capital introduction, for the build of a multi-dimensional quality improving regeneration of the old residential areas in China.